Hollywood's Eve : Eve Babitz and the Secret History of L.A. - Anolik, Lili (New York : Scribner, 2019)
An "account of the birth, adolescence, and adulthood of 20th-century Hollywood through the vivid and unashamed life of Los Angeles-born glamour girl, bohemian, artist, muse, sensualist, wit, and pioneering writer Eve Babitz"--
Includes bibliographic references.
Keywords: Babitz, Eve; Women authors, American -- Biography -- 20th century; Artists -- Biography -- California; Hollywood (Los Angeles, Calif.) -- Biography; Biographies